Anti-HDV seroprevalance among patients with previous HBV infection - Sahin, Abdurrahman; Gurocak, Suzan; Tunc, Nurettin; Demirel, Ulvi; Poyrazoglu, Orhan Kursat; Akbulut, Handan; Bahcecioglu, Ibrahim Halil (Kare Publ, 2018)
OBJECTIVE: This prospective study aimed to determine the prevalence of anti-HDV seropositivity among subjects who had previous hepatitis B virus (HBV) infection. METHODS: Subjects who were admitted to the gastroenterology inpatient clinic of our hospital between August 2016 and July 2017 were screened for previous HBV infection. The subjects who had HBV serology compatible with resolved HBV infection were recruited in the study, and the seroprevalance of anti-HDV was studied. Participants answered a short questionnaire regarding their family history of chronic hepatitis B (CHB) and chronic hepatitis D (CHD) infection and risk factors for transmission. Subjects who were anti-HDV positive were recalled for a control visit, and HBV-DNA and HDV-RNA were assayed in the blood samples of the responders. RESULTS: Among 554 subjects who had previous HBV infection, 53 (9.6%) were anti-HDV positive. The mean age was 63.1 +/- 15.4 years in the anti-HDV-positive group and 65.9 +/- 15.6 years in the anti-HDV-negative group (p=0.19). The most common risk factor for both groups was dental procedures (89% vs 80%, p=0.33). Anti-Hbc IgG, anti-Hbs, and anti-HBeAg seropositivity did not differ between the anti-HDV-positive and -negative groups (for all, p>0.05). Although HDV-RNA was not detectable in all studied samples, only one subject had detectable HBV-DNA in the anti-HDV-positive group. CONCLUSION: This study highlighted the prevalence of anti-HDV among subjects who had resolved HBV infection. Longterm follow-up studies, including after the resolution of both infections, are needed to explore HBV-HDV interactions and the behavioral patterns of these viruses.
Keywords: Anti-HDV; HBV-DNA; HDV-RNA; previous HBV; transmission route